Utility of Next Generation Sequencing in Clinical Primary Immunodeficiencies - Raje, Nikita (Curr Allergy Asthma Rep, 2014)
Primary immunodeficiencies (PIDs) are a group of genetically heterogeneous disorders that present with very similar symptoms, complicating definitive diagnosis. More than 240 genes have hitherto been associated with PIDs, of which more than 30 have been identified in the last 3 years. Next generation sequencing (NGS) of genomes or exomes of informative families has played a central role in the discovery of novel PID genes. Furthermore, NGS has the potential to transform clinical molecular testing for established PIDs, allowing all PID differential diagnoses to be tested at once, leading to increased diagnostic yield, while decreasing both the time and cost of obtaining a molecular diagnosis. Given that treatment of PID varies by disease gene, early achievement of a molecular diagnosis is likely to enhance treatment decisions and improve patient outcomes.